A critical analysis of the Role of Social Media in Shaping National Well-Being - Cristina Dinescu (Syntax Corporation Indonesia, 2023)
Through its impact on a variety of societal factors, such as personal psychological health (PH), community involvement, political debate, and social connection, social media significantly shapes national well-being. Evaluating social media's influence on molding national well-being is essential for resolving its impacts and optimizing its advantages, despite the fact that it may have both good and bad consequences. This research investigates the relationship between adolescents’ psychological health (PH) and social media utilization. The information was collected over the course of several years as part of a research project known as